Effects of drying methods on nutritional and antioxidant properties of tea [Camellia sinensis (L.) Kuntze] leaves and dabai (Canarium odontophyllum Miq.) fruits - Roslan, Ahmad Syazrin (2019)
Hot air drying is the most commonly used method of food presevation but the heat from the process usually destroys their beneficial antioxidant compounds. Alternative methods to hot air drying includes superheated steam drying and freeze drying. Therefore, the objective of this study was to investigate and compare the effects of drying methods on the nutritional and antioxidant properties of tea [Camellia sinensis (L.) Kuntze] leaves and dabai (Canarium odontophyllum Miq.) fruits. Nutrient analysis results for the tea leaves showed significant difference (p<0.05) in the nutrient content obtained from each drying method. Freeze dried tea leaves (FDT) had the highest percentage of moisture (78.35 ± 0.10 %) and fat content (4.91 ± 0.57 %), while superheated steam dried tea leaves (SDT) had the highest percentage of ash (6.05 ± 0.01 %), total dietary fibre (38.29 ± 1.49 %), and total available carbohydrate (1.63 ± 0.13 %). Oven dried tea leaves (ODT) had the highest percentage of protein content (21.24 ± 0.62 %). Nutrient analysis results for the dabai fruit showed significant difference (p<0.05) in the nutrient content obtained from each drying method. Oven dried dabai (ODD) showed the highest percentage of ash (4.70 ± 0.07 %), protein (6.8 ± 0.12 %), and fat content (38.79 ± 1.19 %). Freeze dried dabai (FDD) showed the highest percentage of moisture content (60.78 ± 0.08 %) and total available carbohydrate (3.94 ± 0.01 %), while superheated steam dried dabai (SDD) had the highest percentage of total dietary fibre (55.87 ± 0.13 %). The highest antioxidant capacity, total phenolic, and total flavonoid content were exhibited by FDT and FDD with significant difference (p<0.05). High Performance Liquid Chromatography (HPLC) identified 7 compounds from the tea leaves, and 5 compounds from the dabai fruit. FDT and FDD showed significantly higher (p<0.05) content of these compounds compared to superheated steam and oven dried samples Significantly (p<0.05), Gallic acid had the highest concentration in both samples (5.40 ± 0.02 mg per g DW in FDT, 3.42 ± 0.02 mg per g DW in FDD). At different drying temperatures, SDT dried at 125°C showed significantly higher (p<0.05) antioxidant properties than ODT. ODT dried at 150°C and 175°C showed significantly higher (p<0.05) antioxidant properties than SDT. ODD dried at 125°C showed significantly higher (p<0.05) antioxidant properties than SDD. However, no significant differences (p>0.05) were observed in the antioxidant properties of the fruits dried using both methods at 150°C and 175°C. At different drying durations, SDT dried for 60, 75, and 90 minutes showed significantly higher (p<0.05) antioxidant properties than ODT. In contrast, ODD dried for 60, 75, and 90 minutes showed significantly higher (p<0.05) antioxidant properties than SDD. Overall, FDT and FDD retained the highest antioxidant properties among the samples dried using the three methods. Superheated steam drying method is a better choice than oven drying method for drying tea leaves at varying drying time. In contrast, oven drying method is more suitable for drying the dabai fruit at both varying drying temperature and time.